Revolusi Saintifik dalam Perkembangan Ilmu Optika - Deswita, Pipi; Saputri, Ririn Hustia (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2021)
The scientific revolution is a replacement of the old paradigm to a new paradigm. According to Khun, the key to revolution regarding scientific paradigms is the approach or method taken by scientists in solving scientific problems. One of the paradigms in science is the development of the physics branch of Optics. Optics is the study of the properties of light in a material. This research is a literature study on optics material. The literature is taken from several books and journals related to the research conducted. Based on the search results, it is known that the Scientific Revolution in optics consists of 4 (four) periods. The first period was marked by the discovery of an optical lens. In this first period the opinion of scientists was not accompanied by experiments. The second period scientists have conducted experiments to support the theories put forward. One of the natural phenomena that scientists observed during this period was the rainbow. The third period is the shortest period in the history of the development of optics. In this period Thomas Young explained the concept of light being able to bend which was previously unanswered by Newton's emission theory. The fourth period is the period of modern optics, where the photoelectric effect and fiber optics have been discovered